Baustelle Elektromobilität: Sozialwissenschaftliche Perspektiven auf die Transformation der (Auto-)Mobilität - Haas, Tobias; Brunnengräber, Achim (transcript, 2020)
The turnaround of traffic hyped up - sociological considerations on the transformation of (auto)mobility.